2016
DOI: 10.1111/jnc.13660
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 7 nicotinic receptor coupling to heterotrimeric G proteins modulates RhoA activation, cytoskeletal motility, and structural growth

Abstract: Nicotinic acetylcholine receptors (nAChRs) modulate the growth and structure of neurons throughout the nervous system. Ligand stimulation of the a7 nAChR has been shown to regulate the large heterotrimeric GTP-binding protein (G protein) signaling in various types of cells. Here, we demonstrate a role for a7 nAChR/G protein interaction in the activation of the small (monomeric) RhoA GTPase leading to cytoskeletal changes during neurite growth. Treatment of PC12 cells with the a7 nAChR agonist choline or PNU-28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 75 publications
2
65
0
Order By: Relevance
“…There is increasing evidence, that signaling via nAChR subunit α7 induces Ca 2+ signals and that signaling-related proteins including G proteins can interact with a cytoplasmic loop of this subunit (Kabbani et al, 2013; King and Kabbani, 2016; Valbuena and Lerma, 2016). Similar protein-protein interactions might also occur for subunit α9.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence, that signaling via nAChR subunit α7 induces Ca 2+ signals and that signaling-related proteins including G proteins can interact with a cytoplasmic loop of this subunit (Kabbani et al, 2013; King and Kabbani, 2016; Valbuena and Lerma, 2016). Similar protein-protein interactions might also occur for subunit α9.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been mounting evidence that α7 nAChRs have a large intracellular (Paulo et al, 2009) interactome that may function both as metabotropic as well as ionotropic receptors (de Jonge and Ulloa, 2007; Kabbani et al, 2013; King and Kabbani, 2016), specific signaling intermediaries remain to be identified. The conformational changes induced by the binding of orthosteric ligands may modulate the Jak/Stat cascade, which is implicated in the regulation of inflammation (de Jonge et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…␣7 nAChR has been shown to modulate several signaling pathways, such as JAK2/STAT3/NF-B, PLC/ inositol 1,4,5-trisphosphate, and PI3K/Akt/Nrf-2 pathways, which in immune cells result in potent anti-inflammatory effects through inflammatory cytokine production inhibition and overexpression of hemooxigenase-1 (54,(57)(58)(59). Also, a direct coupling of ␣7 nAChR to G-protein has been recently described (60,61). Thus, our study opens doors to decipher in human NK cells the highly complex signaling pathways triggered by ␣7 nAChR and their association to different cell functions.…”
Section: Discussionmentioning
confidence: 99%